Approximate solution of the Fokker-Planck-Kolmogorov equation - Mitropolskiy, Yu. A. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
For the Fokker-Planck-Kolmogorov equation, the higher approximations are constructed by using the Bogolyubov averaging method.